IMPLEMENTASI MANAJEMEN KELAS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 14 MERANTI - Mozaika, Chintia; Puspita Raya, Mega; Indah Dewi, Novita (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
Classroom management includes teacher skills to create a conducive learning atmosphere so that the learning process is in accordance with the goals to be achieved. By taking a background in SD Negeri 14 Meranti. In the learning process of Islamic Religious Education (PAI) in class, of course there are some students who are noisy and often chat in class with their peers, moving from their seats during the learning process. So this will affect the success of learning objectives. The formulation of the research problem is: how is the implementation of classroom management carried out by the teacher when learning Islamic Religious Education class III at SDN 14 Meranti. The purpose of this study is: to find out how the implementation of classroom management is applied by teachers when teaching PAI class III at SDN 14 Meranti. This type of research is descriptive qualitative. Data collection is done through observation, interviews, and documentation.